How much should incisors be decompensated? periodontal bone defects during presurgical orthodontic treatment in class III double-jaw orthognathic surgery patients. - Kurt Demirsoy, Kevser; Türker, Gökhan; Amuk, Mehmet; Kurt, Gökmen (My University, 2022)
The aims of this study were to evaluate periodontal bone defects around the lower and upper incisors and to identify changes in the buccolingual inclination of the incisors during orthodontic decompensation in skeletal Class III orthognathic surgery patients.

The sample consisted of 26 adults with skeletal Class III deformity who had undergone presurgical orthodontic treatment and orthognathic surgery. Lateral cephalograms obtained before orthodontic treatment and before surgery were used to determine the inclination and position changes of the incisors. Cephalometric measurements were taken using Dolphin Imaging 11.95. Three-dimensional images were generated from cone-beam computed tomography (CBCT) scans prior to surgery and used to detect periodontal bone defects, including fenestration (F) and dehiscence (D).

Intraclass correlation coefficients (ICC) were determined and the measurements showed high reproducibility. The cephalometric data showed normal distribution and there were no differences between genders in terms of cephalometric changes, dehiscence, fenestration, or coexistent (D-F/DF) formation. The patients presented maxillary incisor retroclination and mandibular incisor proclination, which was consistent with the tooth decompensation. CBCT assessment was performed for a total of 208 teeth; while 81 upper and 94 lower incisors had D-F/DF formation, 23 upper and 10 lower incisors were healthy. Statistically significant correlations were not found between the inclination degree of the incisors and D-F/DF formation.

Decompensation of incisors during presurgical orthodontic treatment increases the risk of periodontal defects. There is no linear relationship between the increase in the inclination degrees of incisors and D-F/DF formation.
Keywords: Decompensation; Dehiscence; Fenestration; Incisor inclination; Orthognathic surgery